Efektivitas Program Kekasih Hati (Keluarga Asuh Balita Stunting) dalam Penanganan dan Pencegahan Stunting di Kelurahan Sindangrasa Kec. Ciamis Kab. Ciamis - Fina Fina; Kiki Endah; Regi Refian Garis (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Stunting remains a significant public health issue that affects children’s physical growth, cognitive development, and the overall quality of future human resources. Sindangrasa Village, located in Ciamis District, Ciamis Regency, has implemented the “Kekasih Hati” Program (Foster Family for Stunted Toddlers) as a local initiative to address and prevent stunting. This study aims to describe the effectiveness of the program’s implementation in reducing stunting rates in Sindangrasa Village. This research employs a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation involving key informants engaged in the program’s implementation. Data analysis was conducted using Bormasa’s effectiveness theory, which includes six indicators: goal setting strategy, resource planning and utilization, performance-supportive environment, communication processes, leadership and decision-making, and adaptation and innovation. The findings indicate that the Kekasih Hati Program has not been optimally implemented. This is reflected in low public awareness regarding stunting prevention, limited budget allocation, insufficient program communication, and uneven community participation. Nevertheless, the program has shown positive outcomes, as the number of stunting cases decreased from 10 cases in June 2024 to 6 cases in September 2025. Therefore, strengthening continuous socialization, improving coordination, and optimizing resources are essential to enhance the program’s effectiveness in stunting prevention and management.